(untitled) (Evidence-Based Pharmacotherapy in Clinical Practice, 2025)
Author Mrs Annapurna Anusha Kotwala Assistant Professor, Department of Pharmaceutics, Sultan-ul-Uloom College of Pharmacy, Hyderabad, Telangana, India Abstract Pharmacological management of endocrine disorders requires precise hormone replacement or suppression strategies based on physiological feedback mechanisms. Diabetes management incorporates multiple medication classes including insulin, incretin-based therapies, and oral glucose-lowering agents, with individualized glycemic targets based on patient factors. Thyroid disorder treatment focuses on precise dosing of hormone replacement or suppression therapy with regular monitoring of thyroid function parameters. Adrenal conditions require careful glucocorticoid replacement or suppression protocols with dose adjustments based on physiological requirements and stress conditions. Metabolic syndrome management incorporates multiple interventions targeting individual components including dyslipidemia, hypertension, and insulin resistance. Osteoporosis treatment utilizes antiresorptive and anabolic agents with systematic monitoring of bone mineral density and fracture risk. Drug selection integrates factors including age, comorbidities, contraindications, and specific metabolic parameters. Keywords: Endocrine pharmacotherapy, Diabetes management, Thyroid treatment, Metabolic syndrome, Osteoporosis therapy VIEW PDF